Strategi Komunikasi Politik Digital Tri Andhianto dan Abdul Haris Bobihoe dalam Pilkada Bekasi 2024 - Fitriyanti, Novia; Puspitasari, Ranti; Jasmine, Thalia; Putranto, Algooth (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The 2024 Simultaneous Regional Elections in Bekasi are an important momentum in the development of local democracy in Indonesia, marked by the support of a coalition of ten political parties for the candidate pair Tri Adhianto and Abdul Haris Bobihoe. This study uses a qualitative method with a desk review approach to analyze the communication and campaign strategies of the candidate pair. The results of the study show that this pair succeeded in utilizing social media effectively to reach voters, especially the younger generation. Relevant campaign messages, related to education, job creation, and community welfare, succeeded in building emotional attachment. Their campaign reflects political pragmatism at the local level, where support from various parties puts aside ideological differences in order to achieve electoral goals. Through social media, the candidate pair created two-way communication with the community and expanded their audience reach. This study concludes that adaptive and digital-based campaign strategies can increase public participation and trust in candidates, although challenges in maintaining transparency and accountability remain.